Weekend Surgical Admissions of Pediatric IBD Patients Have a Higher Risk of Complication in Hospitals Across the US. Issue 2 (27th June 2019) - Egberg, Matthew D; Galanko, Joseph A; Kappelman, Michael D
Abstract : Surgical admissions occurring over the weekend have worse clinical outcomes compared with weekday admissions. This study is the first to demonstrate weekend admission as an independent risk factor for in-hospital complication in both pediatric CD and UC hospitalizations. Abstract: Background: Weekend surgical admissions to the hospital are associated with worse clinical outcomes when compared with weekday admissions. We aimed to evaluate the association of weekend admission and in-hospital complications for pediatric inflammatory bowel disease (IBD) hospitalizations requiring urgent abdominal surgery. Methods: We performed a cross-sectional analysis of pediatric (18 years old and younger) IBD hospitalizations between 1997 and 2016 using the Kids' Inpatient Database (KID), a nationally representative database of pediatric hospitalizations. We included discharges with a diagnosis code for Crohn's disease (CD) or ulcerative colitis (UC) undergoing a surgical procedure within 48 hours of admission. We used logistic regression to evaluate the association of weekend admission and complications, controlling for confounding factors. Results: Our study included a total of 3255 urgent surgical hospitalizations, representing 4950 hospitalizations nationwide. The risk difference for weekend CD surgical hospitalizations involving a complication vs weekday hospitalizations was 4%. Adjusted analysis demonstrated a 30% increased risk for complications associated with weekend CD hospitalizations compared with weekday hospitalizations (OR 1.3, 95% CI, 1.0–1.7). The risk difference for weekend UC hospitalizations involving a complication compared with the weekday hospitalizations was 7%. Adjusted analysis demonstrated a 70% increased risk of complication for UC weekend surgical hospitalizations compared with weekday hospitalizations (OR 1.7, 95% CI, 1.2–2.3). Conclusion: Pediatric IBD hospitalizations involving urgent surgical procedures have higher rates of complications when admitted on the weekend vs the weekday. The outcome disparity requires further health services research and quality improvement initiatives to identify contributing factors and improve surgical outcomes.